2011
DOI: 10.1183/09031936.00182410
|View full text |Cite
|
Sign up to set email alerts
|

SERPINE1 -675 4G/5G polymorphism is associated with asthma severity and inhaled corticosteroid response

Abstract: Asthma is characterised by chronic airway inflammation and remodelling, which can be (partially) suppressed by inhaled corticosteroids (ICSs). Plasminogen activator inhibitor-1, encoded by the SERPINE1 gene, is the key inhibitor of the plasminogen activator system, which affects tissue repair and remodelling.We studied associations between a functional SERPINE1 -675 4G/5G promoter polymorphism and asthma development, severity and response to ICSs.Longitudinal cohorts of 281 asthmatics and their nonasthmatic sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 61 publications
0
21
0
3
Order By: Relevance
“…After reading full texts of the remaining 20 articles, twelve were then excluded and eight remained. One article reported two cohorts [14], and each cohort was considered as a separate case-control study. Finally, a total of 9 case-control studies in 8 articles were identified met our inclusion criteria [7][14], including 1817 cases and 2327 controls.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After reading full texts of the remaining 20 articles, twelve were then excluded and eight remained. One article reported two cohorts [14], and each cohort was considered as a separate case-control study. Finally, a total of 9 case-control studies in 8 articles were identified met our inclusion criteria [7][14], including 1817 cases and 2327 controls.…”
Section: Resultsmentioning
confidence: 99%
“…One article reported two cohorts [14], and each cohort was considered as a separate case-control study. Finally, a total of 9 case-control studies in 8 articles were identified met our inclusion criteria [7][14], including 1817 cases and 2327 controls. There were 4 studies of Asians [9], [11]–[13] and 4 studies of Caucasians [7], [8], [10], [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Maior frequência do alelo mutado (53%) foi encontrada em holandeses, e o genótipo 4G/4G estava presente em 28% da população (Dijkstra et al, 2011).…”
Section: Polimorfismo No Gene Do Pai-1 (Serpine1 4g/5g)unclassified